Bending adversity : Japan and the art of survival - Pilling, David (Editor) (London : The Penguin Press, 2020)
Financial Times Asia editor David Pilling presents a fresh vision of Japan, drawing on his own deep experience, as well as observations from a cross section of Japanese citizenry, including novelist Haruki Murakami, former prime minister Junichiro Koizumi, industrialists and bankers, activists and artists, teenagers and octogenarians. Through their voices, Pilling captures the dynamism and diversity of contemporary Japan.
Tsunami. Tsunami ; Bending adversity -- Double-bolted land. Shimaguni ; Leaving Asia -- Decades found and lost. The magic teapot ; After the fall -- Life after growth. Japan as number three ; Samurai with a quiff ; Life after growth ; The promised road ; From behind the screen -- Adrift. Asia ex-Japan ; Abnormal nation -- After the tsunami. Fukushima fallout ; Citizens ; After the tsunami.
"First published in Allen Lane 2014. Published in Penguin Books 2014. Reissued with a new afterword 2020"
Includes bibliographical references (pages 319-348) and index.
AAL
Keywords: Japan -- History -- 21st century; Japan -- Politics and government -- 21st century; Japan -- Economic conditions -- 21st century; Japan -- Social conditions -- 21st century